1970
DOI: 10.1007/bf00167340
|View full text |Cite
|
Sign up to set email alerts
|

The variable X-ray spectrum of Cyg XR-1

Abstract: The variability of the X-ray spectrum of the discrete source Cyg XR-1 (c~ = 19 h 56m) = q-35~ is reviewed. The variations observed in the energy region accessible to balloon borne detectors (energies greater than 20 keV) can be explained by assuming them to be caused by the eclipsing properties of a binary system. It is suggested that the system is composed of a source of small angular extent having a spectrum similar to that of a black body at approximately 1.5 x 108 K (kT= 12.5 keV) and a non X-radiating com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1976
1976

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The radio source is coincident with the 9th mag BOI, HDE 226868 (Webster and Murdin (25), Bolton (26)) which was found to be a spectroscopic binary with a 5-6 day period. The X-ray emission shows no evidence of the 5-6 day binary motion (Tananbaum et al (27)) in spite of earlier claims that it did (Dolan (28,29)). Later spectroscopic studies revealed at least one other spectral line, He n-4686, out of phase with the remainder (Brucato and Kristian (30)).…”
Section: Galactic X-ray Sourcesmentioning
confidence: 92%
“…The radio source is coincident with the 9th mag BOI, HDE 226868 (Webster and Murdin (25), Bolton (26)) which was found to be a spectroscopic binary with a 5-6 day period. The X-ray emission shows no evidence of the 5-6 day binary motion (Tananbaum et al (27)) in spite of earlier claims that it did (Dolan (28,29)). Later spectroscopic studies revealed at least one other spectral line, He n-4686, out of phase with the remainder (Brucato and Kristian (30)).…”
Section: Galactic X-ray Sourcesmentioning
confidence: 92%